A Development of English for Tourism Book Based on Tourism Places in Dompu to Improve Students’ Speaking Skills - Rusdin; Ismail; Safinah; Ulfatun Nuriah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
The aim of this research is to develop a valid, practical, and effective book of English for Tourism based on tourism places in Dompu. This study is a R&D (Research and Development) approach using the 4D model (Define, Design, Develop, and Disseminate). The book that had been developed was implemented in the English learning process at the class XI of Tourism Vocational High School Dompu, Department of Travel and Tourism Business with a total of 27 students, in academic year 2024. The validity test results of the developed book obtained from media expert is 88% (very valid) and 92% (very valid) from material expert. Moreover, the practicality test result from students and teacher was at the level “practical” with average score 3,8 or 76%. Lastly, based on students’ speaking test result, the average total score obtained by 27 students is 77. On other word, 100% students or all 27 students obtained average scores more than or equal to 70. It means all students have successfully done the task with good scores. Based on that, the use of English for tourism book based on tourism places in Dompu is effective to improve students’ speaking skill. Another remarkable finding in this reseach is that both teacher and students strongly agree that the material in book is able to stimulate students to be active in the learning process.